The Effect of Ownership, Good Corporate Governance, and Cash Flows on Company Value with Debt Policy as Mediation in the Manufacturing Sector Pharmaceutical in Indonesia Stock Exchange 2015-2017 - Diana Florenta Butar- Butar; Rusmahweni Rusmahweni (Institute of Computer Science (IOCS), 2022)
This study aims to determine whether ownership affects debt policy, GCG affects debt policy, cash flow affects debt policy, ownership affects firm value, GCG affects firm value, cash flow affects firm value, and whether debt policy is a mediation. the result is ownership and cash flow affect debt policy. ownership, gcg and debt policy affect firm value. and the variable debt policy does not mediate.